Association of Congenital Anomalies in Newborns with Maternal and Fetal Factors in North Gujarat Region, India: A Cross-Sectional Analytical Study - Nilesh Thakor; Dhruv Nimbalkar; Pankaj Nimbalkar (Medsci Publications, 2022)
Background: Approximately 8 to 15% of perinatal deaths and 13 to 16% of neonatal deaths in India are a result of congenital anomalies. The objective of the research was to study incidence of clinically detectable congenital malformations in newborns delivered at secondary and tertiary hospitals and their association with maternal and fetal factors. Material and methods: This study include all new-borns delivered at secondary and tertiary care hospitals in the Mehsana districts of Gujarat, India from January 1st, 2021 to December 31st, 2021. A total of 6900 consecutive births were examined for visible structural anomalies to determine the overall incidence and distribution of congenital malformations and their association with feto-maternal factors. Results: Total numbers of malformed babies were 90 with incidence of 1.30%. Incidence of malformed babies was 1.54% among mother in the age group of 21-35 years, 3.57% among mother with consanguineous marriage, and 6.67.% among mothers with severe anemia. The incidence was 0.97% in babies <1500 birth weight, 0.97% among live births and 12.5% among preterm babies. Conclusion: Congenital anomalies in newborns are significantly associated with maternal factors like maternal age, consanguinity, previous child with malformation, history of previous abortion and severe anemia and fetal factors such as stillbirth, premature babies, and low birth weight.